Microbial contributions to subterranean methane sinks ... : المساهمات الميكروبية في أحواض الميثان الجوفية ... - Jay T. Lennon; Dương Nguyễn-Thùy; N Pham Duc; Agnieszka Drobniak; P Ta Hoa; Phạm Thị; Thomas Streil; Kevin D. Webster; Arndt Schimmelmann (OpenAlex, 2015)
Understanding the sources and sinks of methane (CH4) is critical for predicting and managing global biogeochemical cycles. Recent studies have reported that CH4 concentrations in cave ecosystems are depleted and that these subterranean environments may act as a daily sinks for atmospheric CH4. It has been hypothesized that this CH4 depletion may be caused by radiolysis, an abiotic process whereby CH4 is oxidized via interactions with ionizing radiation derived from radon decay. Alternatively, the depletion of CH4 concentrations could be due to biological processes, specifically oxidation by methanotrophic bacteria. We theoretically explored the radiolysis hypothesis and conclude that it is a kinetically constrained process that is unlikely to lead to the rapid loss of CH4 in subterranean environments. We present experimental results to support this claim. We tested the microbial oxidation hypothesis in a set of mesocosm experiments that were conducted in Vietnamese caves. Our results reveal that ... : يعد فهم مصادر ومصارف الميثان (CH4) أمرًا بالغ الأهمية للتنبؤ بالدورات الكيميائية الحيوية العالمية وإدارتها. أفادت الدراسات الحديثة أن تركيزات الميثان في النظم الإيكولوجية للكهوف قد استنفدت وأن هذه البيئات الجوفية قد تعمل كأحواض يومية للميثان في الغلاف الجوي. وقد افترض أن استنفاد CH4 هذا قد يكون ناجماً عن التحلل الإشعاعي، وهي عملية لاأحيائية يتأكسد فيها CH4 من خلال التفاعلات مع الإشعاع المؤين المشتق من اضمحلال الرادون. بدلاً من ذلك، يمكن أن يكون استنفاد تركيزات الميثان ناتجًا عن العمليات البيولوجية، وتحديدًا الأكسدة بواسطة بكتيريا الميثانوتروفيك. استكشفنا نظريًا فرضية التحلل الإشعاعي وخلصنا إلى أنها عملية مقيدة حركيًا من غير المرجح أن تؤدي إلى الفقدان السريع للميثان في البيئات الجوفية. نقدم نتائج تجريبية لدعم هذا الادعاء. اختبرنا فرضية الأكسدة الميكروبية في مجموعة من تجارب الكون المتوسط التي أجريت في الكهوف الفيتنامية. تكشف نتائجنا أن البكتيريا المغذية للميثان المرتبطة بصخور الكهوف تستهلك CH4 بمعدل 1.33 - 2.70 ملغ CH4 م -2 د -1 . تساوي معدلات أكسدة الميثان هذه أو تتجاوز ما تم الإبلاغ عنه في الموائل الأخرى، ...